Directly inherited partial trisomy of chromosome 6p identified in a father and daughter by chromosome microdissection. Issue 4 (1st April 1999) - Delatycki, Martin B; Voullaire, Lucille; Francis, David; Petrovic, Vida; Robertson, Anne; Webber, Lorna M; Slater, Howard R
Abstract : Cytogenetic analysis of a 4 year old girl with developmental delay and dysmorphic features showed extra chromosomal material of unknown origin on 20p (46, XX, add(20)(p13)). Familial chromosome studies showed direct inheritance of add(20)(p13) from the father, who had a similar, albeit milder, phenotype. Fibroblast chromosome studies of the father showed no karyotype mosaicism. The additional material could not be identified on the basis of the G banding pattern owing to its small size and ambiguous banding pattern. Chromosome microdissection of the unknown material was performed, the DNA was amplified and labelled using degenerate oligonucleotide primed polymerase chain reaction (DOP-PCR) and reverse painted to the proband's cells to show the karyotype 46, XX, der(20)t(6;20)(p23;p13), conferring partial trisomy 6p and presumed partial monosomy for 20p. Chromosome microdissection has made possible the first reported case of directly inherited partial trisomy 6p.